Beyond the orthodox/CAM dichotomy: Exploring therapeutic decision making, reasoning and practice in the therapeutic landscapes of elite sports medicine. (April 2020) - Coveney, Catherine; Faulkner, Alex; Gabe, Jonathan; McNamee, Michael
Abstract: Elite athletes face extreme challenges to perform at peak levels. Acute and chronic musculoskeletal injuries are an occupational hazard while pressures to return to play post-injury are commonplace. Therapeutic options available to elite athletes range from novel 'cutting edge' biomedical therapies, established biomedical and surgical techniques, and physiotherapy, to a variety of non-orthodox therapies. Little is known about how different treatment options are selected, evaluated, nor how their uses are negotiated in practice. We draw on data from interviews with 27 leading sports medicine physicians working in professional football and cycling in the UK, collected 2014–16. Using idea of the 'therapeutic landscape' as a conceptual frame, we discuss how non-orthodox tools, technologies and/or techniques enter the therapeutic landscape of elite sports medicine, and how the boundaries between orthodox and non-orthodox therapy are conceptualised and navigated by sports medicine practitioners. The data provide a detailed and nuanced examination of heterogenous therapeutic decision –making, reasoning and practice. Our data show that although the biomedical paradigm remains dominant, a wide range of non-orthodox therapies are frequently used, or authorised for use, by sports medicine practitioners, and this is achieved in complex and contested ways. Moreover, we situate debates around nonorthodox medicine practices in elite sports in ways that critically inform current theories on Complementary and Alternative Medicine (CAM)/biomedicine. We argue that existing theoretical concepts of medical pluralism, integration, diversity and hybridisation, which are used to explain CAMs through their relationships with biomedicine, do not adequately account for the multiplicity, complexity and contestation that characterise contemporary forms of CAM use in elite sport. Highlights: A wide range of non-orthodox therapies is used in UK elite sports medicine. Global trends and local treatment cultures influence therapeutic practice. Patterns of use, adoption and methods of administration are highly heterogeneous. Mixtures of biomedical and experiential rationales are used to support practices. Our analysis of CAM use challenges a simple orthodox/non-orthodox distinction.